Perguruan Tinggi Islam dalam Mencetak Generasi Ulul Albab - Fatoni, Ahmad (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
Muslims    is    majority  in    the    country    should    gain    the    education quality .Various amendments  and  improvements  in  college  islam  that  should  make us  are  likely to  consider  another self,  and  improve  quality  for  improving  the  qualit y  and  quantity of  islamic  education  in  indonesia. Has  been  commonly known  the presence  of  indonesian  islamic  universities  in  much  of  change,  in line  with the progress  of  knowledge  and  science  and technology .It  is  time  to  college  graduates who can  integrate  I slamic  religion  and  science  in  an  al  quran  with  an  “ulul  albab”.  called.    Indonesian Islamic  universities  in  a  strategic  position  to  get  the   “ulul albab”.